Bioacoustic and biophysical analysis of a newly described highly transparent genus of predatory katydids from the Andean cloud forest (Orthoptera: Tettigoniidae: Meconematinae: Phlugidini). Issue 1 (2nd January 2021) - Woodrow, Charlie; Pulver, Christian; Veitch, Daniel; Montealegre-Z, Fernando
ABSTRACT: Transparency is a greatly advantageous form of camouflage, allowing species to passively avoid detection regardless of the properties of the surface which they occupy. However, it is uncommon and poorly understood in terrestrial species. In one tribe of predacious katydids (Phlugidini), transparency is paired with highly ultrasonic communication for increased predator evasion, yet little is known about the singing capabilities of these species, with only one genus of Phlugidini acoustically well described to date. Here, we describe Speculophlugis hishquten ; a new monotypicgenus of highly transparent crystal katy did here named after the infamous Hish-Qu-Ten from the Predator film franchise, discussing the potential use of this species for non-invasive studies of internal anatomy, and analysing its ultrasonic call. Using laser Doppler vibrometry and light microscopy techniques, we found the transparency of the cuticle around the hearing apparatus to be 85–87% at the wavelength of the laser beam (633 nm), making S. hishquten a candidate for the highest recorded cuticle transparency of any insect. The male song has a fundamental frequency of 50 kHz, matching both the ultrasonic call range and rapid call structure of other Phlugidini species. However, the extent of ultrasonic communication and the level of transparency across the Phlugidini tribe requires more attention.